Isolation and identification of some species of pathogenic bacteria from Periodontitis , dental caries, and root canal inflammation, and the detection of some factors of their virulence (Journal of the College of Basic Education, 2022)
Sixty-two clinical samples were collected from people suffering from oral diseases represented by gum infections, tooth decay and root canal inflammation, under the supervision of a specialized dentist, using sterile cotton swabs, from the place of injury, for auditors of specialized dental centers in the cities of Baghdad and Diyala, for both sexes. As their ages ranged from (5 to 45 years) and for the time period from 24/1/2021 to 25/5/2021. Fifty pathological bacterial isolates were isolated from clinical samples, and the genus Streptococcus appeared in 16 isolates, with a percentage of 32%, which is the largest percentage among other species. They were diagnosed based on the culture and microscopic characteristics, as well as the diagnosis with Vitek2 device for the purpose of diagnosis for the level of species, as the following types were obtained: S.mutans, mitis, S. orilus, S.pyogen, and other types of different bacteria appeared, such as E.faecalis, E.faecium, G.morbilloe, S.aureus, S.epidermidis, S. haemolyticus, E.coli, K.pneumoniae ssp, P.aruginosa, A. baumannii complex. 36 isolates, or 72% of the isolates, showed the ability to produce biofilm by the in-tube method, while 14 isolates were not producing biofilm, with a rate of 28%. The results of the hemolysis test showed that they varied in their ability to produce the hemolytic enzyme. All isolates showed a negative result for the lipolytic enzyme assay. At a rate of 100%. The ability of some isolates to produce urea lytic enzyme appeared, 3 isolates out of the total isolates of 50 isolates, at a rate of 6%. And the ability to produce gelatin lysolytic enzyme. Bacterial isolates showed the ability to produce this enzyme, by 4 isolates, at a rate of 8%. Remarkable results for enzyme production by 30%.